The Development of Online Training Package on Relaxing Massage for Working People in Patum Thani province - เจษฎางค์กูร ณ อยุธยา, ภัทรานิษฐ์; เทพนวล, นฤมล (Journal of Educational Review Faculty of Education in MCU, 2019)
The purpose of this research was 1) to develop the online training package relaxing massage based on the quality and the 80/80 efficiency criteria, 2) to compare the learning achievement before and after training with the online training package on the relaxing massage, and 3) to study learners’ satisfaction towards training with the online training package on relaxing massage. The samples were 30 working people in Khu Khot, Lam Luk Ka District, Pathum Thani province and they were selected by convenient or volunteer sampling. The research instruments were the online training package on relaxing massage, achievement test, and questionnaire. The statistics used to analyze data were mean, standard deviation and t-test for dependent samples. The research result showed that 1) the development of the online training package on relaxing massage was at the good level according to the efficiency criteria 80.00/88.17. 2) The post-test mean scores (18.83) were higher than the pre-test mean scores (14.37) which the learning achievement after training with the online training package was significantly different at the .05 level. 3) The satisfaction of learners towards the online training on relaxing massage was at the most satisfaction level (x = 4.64) as a whole aspect.